Large Tracheocutaneous Fistula Successfully Treated With Bronchoscopic Intervention and Flap Grafting: A Case Report and Literature Review - Li, He-huan; Zhao, Ning; Lu, Jing-wen; Tang, Ru-rong; Liang, Chao-nan; Hou, Gang (Frontiers in Medicine, 2020)
Tracheocutaneous fistula (TCF) is the most common related postoperative complication after tracheotomy. Treatments such as surgery and flap grafting are usually applied to close TCFs. We report a case of a large TCF with an area of approximately 3.0 cm x 1.0 cm. Here, we describe a relatively convenient approach for the management of a patient with a large TCF. In our treatment strategy, a coverd tracheal stent was used to cover the defect by bronchoscopy, the bronchial defect was closed with a local turnover flap, the structure was reinforced with biodegradable material (RapidSorb Plate 2.0), and then transplantation of a deltopectoral flap was performed. It is worth noting that the patency of the trachea was maintained during the whole surgery course. No recurrence or complications occurred after the 12-month follow-up. The large TCF was successfully treated with bronchoscopic intervention, biodegradable material and flap grafting, and without cartilage grafting.